Pseudotumor cerebri in a child with hyperimmunoglobulin E syndrome - Incecik, Faruk; Hergüner, M Ozlem; Altunbaşak, Sakir; Yilmaz, Mustafa (The Turkish Journal of Pediatrics, 2010)
Hyperimmunoglobulin E syndrome (HIES) is recognized as a multisystem disorder with various connective tissue, skeletal and immunologic abnormalities. Central nervous system abnormalities have been considered a feature of HIES. Pseudotumor cerebri (PTC) is a condition characterized by increased intracranial pressure in the absence of any intracranial mass lesion or ventricular dilatation, with normal neurology and cerebral spinal fluid composition. PTC without papilledema is rarely reported in children. We describe an atypical presentation of PTC in a child with HIES.